Religion, spirituality, and mental illness among working professionals: an in-depth interview study - Elliott, Marta (Mental health, religion & culture, 2021)
Religion and spirituality (R/S) tend to be associated with emotional wellbeing, but less is known about how they function in the lives of people with mental illness. This paper presents an analysis of in-depth interviews with 26 adults who self-identified as working professionals with a mental illness. Four themes emerged regarding how R/S was experienced as beneficial to mental health, and three themes regarding how it was problematic. The benefits included providing a sense of belonging, a sense of purpose, supportive relationships with R/S figures, and therapeutic R/S practices, whereas problematic aspects included religion as a risky refuge, religious struggles, and abuse in religious settings. In addition, 21 of 26 reported transitions related to their mental illness including switching between religions, leaving religion, and becoming more spiritual, leaving R/S altogether, and religious conversion. The results are discussed, and implications are drawn for R/S practitioners as well as for future research.